2018
DOI: 10.1186/s12955-018-0887-x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits in pain perception, ability function and health-related quality of life in patients with failed back surgery syndrome undergoing spinal cord stimulation in a clinical practice setting

Abstract: BackgroundFailed back surgery syndrome (FBSS) represents one main cause of chronic neuropathic or mixed pain, functional disability and reduced Health Related Quality of Life (HRQoL). Spinal Cord Stimulation (SCS) can be a value for money option to treat patients refractory to conventional medical management (CMM).We estimated from real-world data: 1) the amount of reduced levels of HRQoL of target patients compared to general population, 2) the relationship between pain intensity, functional disability, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
2
19
1
Order By: Relevance
“…Importantly, the evolution of patients after SCS related to routine activities improved dramatically after the 3-month, and kept constant during all 12-month period evaluation. Although in the present study the improvement of functional capability was demonstrated after the 3-month, Scalone L et al (2018) described that pain, functional disability and Health Related Quality of Life significantly reached improvement after 6 months from SCS and generally remained stable during the 2-year follow-up [12]. In contrast, our population in this actual study demonstrated an improvement of pain after 1 month, improvement of functional disability after the 3-month.…”
Section: Discussioncontrasting
confidence: 73%
“…Importantly, the evolution of patients after SCS related to routine activities improved dramatically after the 3-month, and kept constant during all 12-month period evaluation. Although in the present study the improvement of functional capability was demonstrated after the 3-month, Scalone L et al (2018) described that pain, functional disability and Health Related Quality of Life significantly reached improvement after 6 months from SCS and generally remained stable during the 2-year follow-up [12]. In contrast, our population in this actual study demonstrated an improvement of pain after 1 month, improvement of functional disability after the 3-month.…”
Section: Discussioncontrasting
confidence: 73%
“…The EQ VAS of FBSS patients before salvation is 51.1 (±20.3) in this study. This is significantly higher than the novo SCS patients, as reported in the study of Scalone et al with an EQ VAS of 37.4 [ 32 ]. EQ VAS comparison between our baseline results (51.1(±20.3)) and the results of Scalone et al at 12 months of SCS (55) only indicates a small difference although patient satisfaction with SCS was highly incomparable.…”
Section: Discussionmentioning
confidence: 60%
“…FBSS patients, prior to SCS implantation, report pain and limited capabilities as the greatest impairments of their quality of life. In a recent study by Scalone et al, 65% of FBSS patients reported on the EQ5D-3L extreme problems on the subdomain of “pain”, whereas 41.3% reported extreme problems on the subdomain of “usual activities” [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a comparative study between SCS and repeat surgery, the effect of SCS was superior to surgery for the alleviation of nerve root compression 3 . After the compelling randomized controlled study of North et al, 3 several studies confirmed the reduction of pain scores with SCS 1,4–6 …”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain caused by failed back surgery syndrome (FBSS) is associated with a higher pain score, lower health‐related quality of life (HRQoL), and higher functional disability when compared with the general population 1 . Compared to patients suffering from other chronic pain (eg, complex regional pain syndrome, rheumatoid arthritis, osteoarthritis, and fibromyalgia), patients with FBSS have higher pain scores and a lower HRQoL 2 …”
Section: Introductionmentioning
confidence: 99%